Електронні докази у кримінальному процесі: проблемні питання теорії та практики - Фоміна, Т. Г.; Fomina, T. H.; Рачинський, О. О.; Rachynskyi, O. O.; Тетяна Фоміна (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 3 (102), ч. 2. - С. 207-220, 2023)
Узагальнено наукові напрацювання щодо поняття, сутності електронних доказів і надано авторське визначення поняття «електронний (цифровий) доказ» у кримінальному провадженні. Досліджено нормативно-правове регулювання використання електронних (цифрових) доказів у кримінальному провадженні. Проаналізовано слідчо-судову практику, а також практику Верховного Суду щодо визнання допустимості таких доказів у кримінальному провадженні.

The article summarises the scientific developments regarding the concept and essence of electronic evidence and provides the author’s own definition to the concept of “electronic (digital) evidence” in criminal proceedings; examines the regulatory framework for the use of electronic (digital) evidence in criminal proceedings; analyses the investigative and judicial practice and the practice of the Supreme Court regarding the admissibility of such evidence in criminal proceedings. It has been admitted that today the problem of regulating electronic (digital) evidence is relevant. The analysis of the Criminal Procedure Code of Ukraine makes it possible to understand that electronic (digital) evidence has almost no legal regulation, which negatively affects the quality and effectiveness of criminal proceedings. As a result, a number of legislative contradictions arise. Unlike other procedural laws (commercial, civil and administrative), criminal procedural legislation does not contain any provisions on electronic (digital) evidence. At the same time, there are positive trends at the legislative level to recognise the need to regulate electronic (digital) evidence in criminal proceedings. It has been determined that today there is no unified approach among scholars to understanding the concept, features and place of electronic evidence in the system of sources of evidence in criminal proceedings. It is proposed to use the term “electronic (digital) evidence” at the legislative level. This is substantiated by the fact that “electronic” indicates the type of device with which the evidence was created and stored, and “digital” refers to the type of recording the formation on the relevant device. The analysis of investigative and judicial practice has highlighted the ambiguity in the understanding of law enforcement officers regarding the collection of electronic evidence. This issue was the subject for consideration by the judges of the Criminal Court of Cassation of the Supreme Court (in particular, the procedure for assessing electronic evidence and its admissibility was explained in the decision of the Joint Chamber of the Criminal Court of Cassation of the Supreme Court dated 29 March 2021 in case No. 554/5090/16-к). Taking into account international experience in collecting electronic (digital) evidence allows the use of the Berkeley Protocol in criminal proceedings in Ukraine, as it is actively used by the international community and is relevant in the context of russia’s armed aggression against Ukraine.

Обобщены научные наработки относительно понятия, сущности электронных доказательств и авторское определение понятия «электронное (цифровое) доказательство» в уголовном производстве. Исследовано нормативно-правовое регулирование использования электронных (цифровых) доказательств в уголовном производстве. Проанализирована следственно-судебная практика, а также практика Верховного Суда по признанию допустимости таких доказательств в уголовном производстве.
Electronic evidence in criminal proceedings: problematic issues of theory and practice
Keywords: кримінальне провадження; докази; процес доказування; електронний доказ; цифровий доказ; допустимість доказів; criminal proceedings; evidence; process of proof; electronic evidence; digital evidence; admissibility of evidence; уголовное производство; доказательства; процесс доказывания; электронное доказательство; цифровое доказательство; допустимость доказательств